New Boots for Bob! - Thorpe, Kiki; Redmond, Diane (New York, 2003)
Bob has a new pair of boots that make a funny squeaking sound when he walks.
Based upon the television series Bob the Builder(tm) created by HIT Entertainment PLC and Keith Chapman, as seen on Nick Jr.